Vyankatesh Balaji Temple - Ghosh, Ayan (2023)
Built-in 1781, during the period of Peshwa rule in the Deccan, the Vyankatesh Balaji Temple is a typical Peshwa-style temple, with its arched nagarkhana gateway, Mangalore tiled roofing, and a high domed roof. Inside, there is a courtyard and dharamshala, still occupied by the family of the pujaris who maintain the temple. The layout of the site is asymmetric, and the gateway is placed off-center due to this peculiar arrangement.